Achter spreekgestoelte: De Swaan. 1e rij v.l.n.r. : Van Kemenade, Den Uyl, Noorman-den Uyl, Ariane den Uyl, Noorman, Ter Beek, Pronk. 2e rij: ?, ?, Sint, ?, Ter Veld, Wallage, Beck, Jessie Beck, Alders - Verberne, George,
Achter spreekgestoelte: De Swaan. 1e rij v.l.n.r. : Van Kemenade, Den Uyl, Noorman-den Uyl, Ariane den Uyl, Noorman, Ter Beek, Pronk. 2e rij: ?, ?, Sint, ?, Ter Veld, Wallage, Beck, Jessie Beck, Alders.